Micropropagation of Salvia broussonetii Benth. - A Medicinal Plant Species - Mederos-Molina, S (Plant Tissue Culture and Biotechnology, 2008)
The purpose of this study was to establish culture medium requirements for micropropagation of Salvia broussonetii Benth., an important medicinal plant. Cultures were initiated from axillary shoots collected from mature plants. Most satisfactory results were achieved using a MS.2 medium supplemented with 1 mM ascorbic acid, 1.44 µM GA3 and 1.11 µM BAP. Axillary nodes were used for in vitro regeneration of multiple shoots and best results were achieved with MS.2 medium plus 1.44 µM GA3, 2.66 µM BAP and 1.14 µM IAA. Shoots rooted without symptoms of chlorosis or necrosis in half-strength MS.2 medium plus 1.44 µM GA3 and 2.28 µM IAA. Key words: Axillary shoots, Micropropagation, Medicinal plant, Salvia broussonetii DOI = 10.3329/ptcb.v16i1.1101 Plant Tissue Cult. & Biotech. 16(1): 19-23, 2006 (June)